Challenges of the Execution of Hospital Accreditation in Iran: A Critical Review - Jamshid Bahmaei; Peivand Bastani; Ali Keshtkaran; Mohammadtaghi Mohammadpour; Yaser Sarikhani (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Accreditation is a method used for the improvement of the quality of hospital services. It refers to the systematic evaluation of the health centers based on specific standards. The present study aimed to critically review the implementation of accreditation standards in hospitals. Methods: This critical review investigated all the articles that were published during 1993-2019. In order to find the sources, the authors referred to various databases, namely ISC, DOAJ, PubMed, ProQuest, Embase, Science Direct, Scopus, and Web of Science. The keywords used for the search included Mesh terms and common keywords related to the subject of the study, including challenges, barriers, hospital management, accreditation, hospital, or accreditation hospital. Finally, the full texts of 16 articles were reviewed for the purposes of the study.  Results: According to the results, various issues, such as the accreditation organization independence, staff and physician participation, number, structure, and content of standards, structural and contextual problems, importance of human resources, financial and capital resources, organizational and management issues, other plans, role of evaluators and their evaluation methods, role of stakeholders, and impact of accreditation on the patients and teaching atmosphere of the hospital were executive challenges of hospital accreditation. Conclusion: In order to increase the impact of accredition and significantly address its challenges, there should be emphasis on performance indicators, preparation by training and raising awareness of the personnel, budget allocation, and development of plans on accreditation.